Member Satisfaction With The Role of The Kuantan Singingi Rubber Farmers Association (APKARKUSI) in The Rubber Trade Using CSI AND IPA Methods - Meli Sasmi; Agustar, Asdi; Syarfi, Ira Wahyuni; Hasnah, Hasnah (Business Review and Case Studies, 2024)
Background: Farmer associations are agricultural commodity institutions that fight for the interests of farmers. The association is seen as the right strategy to empower farmers and is expected to satisfy its members. However, the functions and objectives carried out by farmer associations in the context of agriculture, which should be a forum to improve the welfare of farmers, sometimes face challenges in carrying out their role effectively. The scope of this research is related to its role in the business system, which includes five indicators, namely its role in increasing knowledge, dissemination, facilitation, advocacy, and monitoring and evaluation. Purpose: The research analyzes members’ satisfaction with APKARKUSI’s role in the rubber trading system. Design/methodology/approach: The research approach uses a survey. The research sample is a member of APKARKUSI, namely 5 POKTAN and 5 GAPOKTAN, 30 respondents from POKTAN and GAPOKTAN management. Primary and secondary data are used. Primary data was obtained using a list of questions, and validity and reliability tests were carried out. The methods used are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) analysis. Findings/Results: There are four roles of APKARKUSI, according to important members, but the performance of APKARKUSI is not good; as many as thirteen roles according to important members and good performance, two roles according to members are not important and performance is also not good, six roles according to members are not important but good performance. The results of the CSI analysis of the role carried out by APKARKUSI as a whole have satisfied members. Conclusion: The role played by APKARKUSI in the rubber trading system, there are still those who have not given satisfaction to members, so APKARKUSI still needs to improve its performance towards this role. Originality/value (State of the art): APKARKUSI, as a rubber farmers association, can be one of the institutional concepts to realize agricultural development. Keywords: farmer satisfaction, farmer association, rubber trade, importance performance index, customer satisfaction index